THE RELATIONSHIP OF DISTANCE TO HEALTH FACILITIES AND PHYSICAL ACTIVITIES IN RELATION TO THE QUALITY OF LIFE OF POSTMENOPAUSAL WOMEN - adella wahyuningsih; Tiyas Kusumaningrum; Gadis Meinar Sari (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2021)
Quality of menopaused women’s life is influenced by several factors such as age, education level, occupation, and physical activity. Quality of life has concepts such as physical well-being, functional ability, and emotional or social well-being which ultimately lead to changes in individuals. Objective: to analyze factors related to the quality of postmenopausal women’s life. Methods: This observational analytic study used a cross sectional design. The population was all postmenopausal women who filled out online questionnaires using google forms distributed through social media with a sampling technique of convenience sampling with a total of 56 respondents. The instruments used in this study were the MENQoL (Menopause Specific Quality of Life) questionnaire and the husband's support questionnaire. Data were analyzed by using Chi Square Test. Results: This study showed that there was a relationship of physical activity which had a significant value of (p= 0.001) and the distance to health facilities (p= 0.043) to the quality of life of postmenopausal women. Conclusion: Physical activity and distance to health facilities affect the quality of life of postmenopausal women.